FORENSIC ASSESSMENT OF GUNSHOT INJURIES IN MAIDAN NEZALEZHNOSTI PROTESTERS - Mishalov, V.D.; Petroshak О.Yu.; Hoholyeva, T.V.; Gurina О.O.; Gunas V.І. (World of Medicine and Biology, 2019)
Over the last 5 years, the number of gunshot injuries in Ukraine has increased. The information about the peculiarities of bodily harm in the protesters of the Maidan Nezalezhnosti in Kyiv in 2014 remains relevant. The purpose of the study was to analyze the peculiarities of injuries sustained by Euromaidan protesters on February 18-20, 2014. The material of the study was archival materials ("Specialist conclusions") of the Department of Forensic Medicine of the Shupyk national medical academy of postgraduate education with the results of the investigation of injuries of 322 injured protesters on February 18-20, 2014 in Kyiv. Research methods were used: anthropometric, morphometric and photographic. The largest number among the victims made up men with gunshot injuries, caused by elastic bullets and a buckshot, lead meal and a buckshot, a 12 mm “Blondo” type metal ball; thermal, chemical burns; contusions, loss of vision and hearing, traumatic amputations of the fingers caused by stun grenades. There were injuries caused by police batons, sticks, fists and feet. The nature, volume and predominant localization of the damages (lower extremities and head) indicate that the stun grenades were intentionally and artificially completed with additional striking components. Light injuries were dominated by degree of severity. Among the injuries in 322 victims of the Euromaidan protesters during the events of February 18-20, 2014, the largest number consisted of manifestations of gunshot injuries: bruises, bleeding, wounds caused by elastic bullets and a bullet to a "non-lethal" weapon and lead buckshot and buckshot, 12mm “Blondo” metal ball; thermal, chemical burns, contusions, loss of vision and hearing, traumatic amputations of the fingers caused by stun grenades.